FIGHTING FOR AFRICAN RESOURCES: „OIL” ASPECT OF SUDAN CRISIS - Шуляк, С.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In this article the author examines Sudan crisis as a part of the leading world nation’s fighting for African natural resources. In particular the role of „oil” factor is underlined in the rivalry between China and USA. The positions of China, the USA and France concerning the conflicts in Southern Sudan and Darfur are analyzed.